2022
DOI: 10.1115/1.4052924
|View full text |Cite
|
Sign up to set email alerts
|

Proper Orthogonal Decomposition Based on Vorticity: Application in a Two-Phase Slug Flow

Abstract: Large-scale turbulent flow features in liquid (water) and gas (air) phases in the film region of two-phase slug flow were identified by using proper orthogonal decomposition (POD) of the vorticity fields. Linear combination of POD vorticity modes is used for the qualitative visualization of coherent structures. The vorticity fields are computed from the instantaneous two-dimensional velocity fields measured using a combined particle image velocimetry and laser-induced fluorescence technique (PIV-LIF). Vorticit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…Vorticity is generally regarded as the most widely used vortex identification method [7].These days, Q-criterion [8] and omega vortex identification method [9] are also adopted to identify the vortex structure in the investigation of hydrofoil and hydraulic machinery. Liu et al [10] proposed the conception of Rortex, which can accurately identify the rigid rotational part in vortex.…”
Section: Introductionmentioning
confidence: 99%
“…Vorticity is generally regarded as the most widely used vortex identification method [7].These days, Q-criterion [8] and omega vortex identification method [9] are also adopted to identify the vortex structure in the investigation of hydrofoil and hydraulic machinery. Liu et al [10] proposed the conception of Rortex, which can accurately identify the rigid rotational part in vortex.…”
Section: Introductionmentioning
confidence: 99%
“…Similar properties with respect to POD convergence may therefore be expected, providing the basis for comparison between results found in the present work and comparable results on enstrophy-based POD found in literature. Enstrophy-based POD was utilized by Huang (1994) and by Kostas, Soria, and Chong (2005) for identifying coherent flow structures from 2D particle image velocimetry (PIV) measurements of a backward-facing step flow, and similarly by Munir et al (2022), based on 2D measurements of two-phase slug flow made by combining PIV and laserinduced fluorescence. Sengupta et al (2015) demonstrated reduced-order modeling of a flow past a cylinder applying enstrophy-based POD to 2D DNS data, using the resulting modes in a vorticity-formulation of the Navier-Stokes equations.…”
Section: Introductionmentioning
confidence: 99%
“…As previously observed, POD has been used in two-phase applications. In particular, some authors [16][17][18][19][20] have applied this specific technique to identify the dominant structures in the flow dynamics of horizontal slug flow commonly observed in many industrial processes. Both phases, the liquid (water or oil) and the gaseous, have been explored.…”
Section: Introductionmentioning
confidence: 99%